The Concept of Morals and Behavior According to Nursi - Peshraw Hama Ali Abdullah; Abdlfattah Hussein Sulaiman (QALAAI ZANIST JOURNAL, 2023)
Those who follow Turkey’s modern history will find that after Ottoman Empire it suffered a massive setback in its creed. This came after the seculars used all their power and changed it from the Islamic Empire, whose constitution is derived from the Quran, to the secular state. During this era, Imam Said al-Nursi may God have mercy on him, defended Islam and its creed and laws with all courage. Among his jihad and his call to God’s way, he composed Risale-i Nur, which was a torch to the darkness of atheism and ambiguity that surrounded that era. Because there were not any printers at that time, his student wrote it with their hand and published it among people, so the Muslims read it with all passion and they relived by its content, so it renewed their faith and their hearts becomes stronger in bearing the burdens of that time. Therefore it’s a matter of faithfulness to scholars to study his works in various fields. Our modest study is on some moral foundations in his work. And we choose (The Concept of Moral and behavior from Nursi’s View) as its title. Our work consists of an introduction and two chapters: the first chapter is dedicated to the characteristics of moral education according to Nursi, and the second chapter deals with Sources of good morals in Al-Nursi’s view. Then the conclusion recorded some results. And I ask God to accept it from me as a good effort, and my last word is Praying to my Lord.